Perbedaan Tingkat Kecemasan Antara Siswi Dengan Berat Badan Normal Dan Overweight di SMA Batik 1 Surakarta. - , Adelina, dr. Rh. Budhi Muljanto, Sp. KJ, dr. Dodik Nursanto (2015)
Background : Psychological disorder that's happening around girls and children is quite common, especially girls. In their earlier teenagers years, especially girls, they started to took notice about their appearances, ideal nody shape not just for asthetic pleasure but also to prevent the risk of having an illness that comes from being overweight. Objective : To determine the difference of anxiety level between female students with normal weight and overweight of SMA Batik 1 Surakarta. Methods : This study of research used analytic observation with cross sectional approach that's done on 96 female student in SMA Batik 1 Surakarta. Consisted of 48 student with normal body weight and 48 student with over body weight. The respondent was chosen with purposive sampling, and then collecting data about their weight and height. For then the responder was given questionnaire L-MMPI and T-MAS. The data have been obtained was analyzed using unpaired t test throught SPSS version 21 for windows. Results : Based on the analysis of data has been obtained using unpaired t test showed p = 0,000 (p